Challenging the Hemodynamic Hypothesis in Heart Failure With Preserved Ejection Fraction: Is Exercise Capacity Limited by Elevated Pulmonary Capillary Wedge Pressure?. Issue 5 (16th December 2022) - Sarma, Satyam; MacNamara, James P.; Balmain, Bryce N.; Hearon, Christopher M.; Wakeham, Denis J.; Tomlinson, Andrew R.; Hynan, Linda S.; Babb, Tony G.; Levine, Benjamin D.
Abstract : Background: Exercise intolerance is a defining characteristic of heart failure with preserved ejection fraction (HFpEF). A marked rise in pulmonary capillary wedge pressure (PCWP) during exertion is pathognomonic for HFpEF and is thought to be a key cause of exercise intolerance. If true, acutely lowering PCWP should improve exercise capacity. To test this hypothesis, we evaluated peak exercise capacity with and without nitroglycerin to acutely lower PCWP during exercise in patients with HFpEF. Methods: Thirty patients with HFpEF (70±6 years of age; 63% female) underwent 2 bouts of upright, seated cycle exercise dosed with sublingual nitroglycerin or placebo control every 15 minutes in a single-blind, randomized, crossover design. PCWP (right heart catheterization), oxygen uptake (breath × breath gas exchange), and cardiac output (direct Fick) were assessed at rest, 20 Watts (W), and peak exercise during both placebo and nitroglycerin conditions. Results: PCWP increased from 8±4 to 35±9 mm Hg from rest to peak exercise with placebo. With nitroglycerin, there was a graded decrease in PCWP compared with placebo at rest (–1±2 mm Hg), 20W (–5±5 mm Hg), and peak exercise (–7±6 mm Hg; drug × exercise stage P =0.004). Nitroglycerin did not affect oxygen uptake at rest, 20W, or peak (placebo, 1.34±0.48 versus nitroglycerin, 1.32±0.46 L/min; drug × exercise P =0.984). Compared with placebo, nitroglycerin lowered stroke volume at rest (–8±13 mL) and 20W (–7±11 mL), but not peak exercise (0±10 mL). Conclusions: Sublingual nitroglycerin lowered PCWP during submaximal and maximal exercise. Despite reduction in PCWP, peak oxygen uptake was not changed. These results suggest that acute reductions in PCWP are insufficient to improve exercise capacity, and further argue that high PCWP during exercise is not by itself a limiting factor for exercise performance in patients with HFpEF. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT04068844.